Reviewer Acknowledgements - Williams, Richard (Journal of Agricultural Studies, 2021)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 9, Number 3 Ahmad Reza Pirali Zefrehei, Gorgan University, Iran Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil Alexandru Ioan Apahidean, Univ. of Agricultural Sciences and Veterinary Medicine, Romania Ana Daniela Lopes, Universidade Paranaense, Brazil Anca-Luiza Stanila, ICPA, Romania André Luiz Rodrigues Magalhães, UFAPE, Brazil Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Benard Kiplangat Rop, University of Nairobi, Kenya Camilla H. M. Camargos, University of Campinas, Brazil Cleber Duarte, University of Guararapes, Brazil Darwin Pangaribuan, University of Lampung, Indonesia Eben von Well, Agricultural Research Council, South Africa Eliana Mariela Werbin, National University of Cordoba, Argentinian Emmanuel E. Omeje, University of Nigeria, Nigeria Eric Krawczyk, University of Michigan, USA Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Fernando Rodrigues de Amorim, State University of Paulista (UNESP), Brazil Guitong Li, China Agricultural University, China Habu Saleh Hamisu, National Horticultural Research Institute, Nigeria Hedayatollah K. Soureshjani, Ferdowsi University of Mashhad, Iran Jacquelin Teresa Camperos Reyes, São Paulo State University (UNESP), Brazil Jorge A. López, University Tiradentes, Brazil Juliana Nneka Ikpe, Akanu Ibiam Federal Polytechnic, Nigeria Luh Suriati, Warmadewa University, Indonesia Mahyar Gerami, Sana Institute of Higher Education, Iran María Francisca Perera, ITANOA, EEAOC-CONICET, Argentina Mariana Esteves, Luiz de Queiroz College of Agriculture University of Sao Paulo, Brazil Mohamed Mattar, King Saud University, Saudi Arabia Mohammed El Basuini, Kagoshima University, Japan Mohammed Jamal Uddin, Bangladesh Agricultural Research Institute (BARI), Bangladesh Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Olga Mykhailenko, National University of Pharmacy, Ukraine Radu Liviu Sumalan, University of Agricultural Sciences and Veterinary, Romania Raul Pașcalău, Banat's University, Romania Saiful Irwan Zubairi, Universiti Kebangsaan Malaysia (UKM), Malaysia Sarir Ahmad, Abdul Wali Khan University, Pakistan Shubha Kumari, ICAR-RCER, India Sina Nabaei, Azad University, Iran Sudu Hakuruge Pushpa Malkanthi, Sabaragamuwa University of Sri Lanka, Sri Lanka Sybelle Mesquita Silva, Universidade Federal de Alagoas, Brazil Toncho Gospodinov Penev, Trakia University, Bulgaria Tugay Ayasan, Osmaniye Korkut Ata University, Turkey Utkarsh R. Moon, Mahatma Gandhi College of Science, India Zakaria Fouad Abdallah, National Research Centre, Egypt Zeinab Mohammadi Shad, Iowa State University, USA Zhao Chen, Clemson University, USA Richard Williams Editorial Assistant Journal of Agricultural Studies -------------------------------------- Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Fax: 1-702-420-2900 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org